Trauma patients' rights during resuscitation - J.C. Bruce (AOSIS, 2000)
Doctors and nurses working in hospital emergency departments face ethical and moral conflicts more so than in other health care units. Traditional curricular approaches to health professional education have been embedded in a discriminatory societal context and as such have not prepared health professionals adequately for the ethical realities of their practice. Furthermore, the discourse on ethical theories and ethical principles do not provide clear-cut solutions to ethical dilemmas but rather serve as a guide to ethical decision- making. Within the arena of trauma and resuscitation, fundamental ethical principles such as respect for autonomy, beneficence, non-maleficence and justice cannot be taken as absolutes as these may in themselves create moral conflict. Resuscitation room activities require a balance between what is " ethically" correct and what is "pragmatically required" . Because of the urgent nature of a resuscitation event, this balance is often under threat, with resultant transgression of patients' rights. This article explores the sources of ethical and moral issues in trauma care and proposes a culture of human rights to provide a context for preserving and protecting trauma patients' rights during resuscitation. Recommendations for education and research are alluded to in concluding the article.